Local or general anesthesia for carotid endarterectomy: Which anesthesia technique should be preferred? - Çayır, Mustafa Çağdaş; Yüksel, Ahmet (Journal of Surgery and Medicine, 2020)
Aim: Carotid endarterectomy is performed in order to prevent disability or fatal stroke in patients with carotid stenosis. The objective of this study was to analyze and compare patients undergoing carotid endarterectomy under general or local anesthesia, and to determine whether the local anesthesia method is superior to general anesthesia in terms of postoperative morbidity and mortality. Methods: A total of 80 patients who underwent carotid endarterectomy due to significant carotid arterial stenosis under general or local anesthesia in the cardiovascular surgery clinic of our hospital between November 2016 and January 2019 were included in this prospective cohort study. Forty carotid endarterectomy operations were performed under general anesthesia and 40 under local anesthesia. The study groups were divided as the general anesthesia group and local anesthesia group. Both groups were compared in terms of sociodemographic characteristics, preoperative risk factors, postoperative complications, operation time and length of hospital stay. Results: No statistically significant difference was found between the two groups in terms of age and gender (P=0.665, P=0.636; respectively). The groups were similar in terms of the rate of asymptomatic patients, stroke or myocardial infarction, postoperative complications including minor stroke, cranial nerve damage, hematoma and internal carotid artery occlusion (P=0.264, P=0.780,P=1.000, P=0.870, P=0.870, P=1.000, P=0.723, respectively). The mean operation time and length of hospital stay were statistically significantly shorter in the local anesthesia group compared to general anesthesia group (P<0.001, P=0.655; respectively). Conclusion: Local anesthesia provided shorter operation time and length of hospital stay for carotid endarterectomy procedure. Further comprehensive prospective studies are needed to clarify benefits of the use of local anesthesia for carotid endarterectomy.